1991
DOI: 10.1093/nar/19.21.5929
|View full text |Cite
|
Sign up to set email alerts
|

One base pair change abolishes the T cell-restricted activity of a kB-like proto-enhancer element from the interleukin 2 promoter

Abstract: The inducible, T cell-specific enhancers of murine and human Interleukin 2 (Il-2) genes contain the kB-like sequence GGGATTTCACC as an essential cis-acting enhancer motif. When cloned in multiple copies this so-called TCEd (distal T cell element) acts as an inducible proto-enhancer element in E14 T lymphoma cells, but not in HeLa cells. In extracts of induced, Il-2 secreting El4 cells three individual protein factors bind to TCEd DNA. The binding of the most prominent factor, named TCF-1 (T cell factor 1), is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

1993
1993
2000
2000

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 36 publications
1
30
0
Order By: Relevance
“…The latter are binding sites for positive-acting transacting factors. When these sites are cloned in multiple copies in front of an indicator gene, they exhibit an inducible, T-cell-restricted activity like that of the entire IL-2 enhancer (4,5,35,42). Previously, we and others showed that CsA and FK506 selectively inhibit the activity of purine boxes, the binding site of the lymphoid-specific factor NFAT-1, and of the UPS (4, 10, 35) when they are added to the cells at the same time as (or after) the inducers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter are binding sites for positive-acting transacting factors. When these sites are cloned in multiple copies in front of an indicator gene, they exhibit an inducible, T-cell-restricted activity like that of the entire IL-2 enhancer (4,5,35,42). Previously, we and others showed that CsA and FK506 selectively inhibit the activity of purine boxes, the binding site of the lymphoid-specific factor NFAT-1, and of the UPS (4, 10, 35) when they are added to the cells at the same time as (or after) the inducers.…”
Section: Resultsmentioning
confidence: 99%
“…All recombinant DNA work was done by standard procedures (38). The construction of the protoenhancer constructs 5 xUPS, 5 xTCEd, and 4xPu-bd, containing multimers of the protein-binding sites of the IL-2 enhancer in front of the thymidine kinase (tk) promoter of CAT vector pBLCAT2, has been described before (4,5,35,42). Construct 5XUPS carries five copies of the UPS, spanning nucleotides from positions -64 to -94 of the IL-2 enhancer (4) (see Fig.…”
Section: Methodsmentioning
confidence: 99%
“…This transcription factor plays an important role in activating the IL-2 promoter in T cells (Hoyos et al, 1989;Shibuya et al, 1989;Baumann et al, 1991;Briegel et al, 1991) (and Figure 3) as well as numerous other promoters, in many cell types (Baeuerle, 1991). Therefore understanding how calcineurin activates NF-xB might provide generalizable insights into the mechanisms by which this transcription factor is controlled.…”
Section: Discussionmentioning
confidence: 99%
“…DNA sequences recognized by these factors are found within the 300 base pairs preceding the IL-2 gene transcription start site. There are minimally five factors, uniquely defined by nucleotide sequence recognition, essential for (ionomycin+PMA)-induced transcription from the IL-2 gene promoter: NF-AT, which binds the IL-2E element (Durand et al, 1988), NF-xB, which binds the IL-2C element (Baumann et al, 1991;Briegel et al, 1991;Hoyos et al, 1989;Shibuya et al, 1989), which recognizes a sequence within the IL-2B element (Jain et al, 1992a,b;Northrop et al, 1992), and OAP (Ullman et al, 1991) and Oct-I (Kamps et al, 1990), which function together, each recognizing an independent sequence within the IL-2A element (Durand et al, 1988 (Mattila et al, 1990). (ii) An NF-xB-dependent enhancer is responsive to PMA, unresponsive to ionomycin, but very responsive to ionomycin in the presence of PMA.…”
Section: Introductionmentioning
confidence: 99%
“…Several factors other than NF-κB have been shown to interact with NF-κB-like motifs, including AP-3, MP-1, PRDII-BF1, HIV-EP1 and MBPII [35][36][37][38][39]. Briegel et al [40] showed that TCF-1 binds more strongly than NF-κB to an NF-κB-like motif (TCEd) in the interleukin 2 promoter. They demonstrated that the conversion of TCEd to a perfect NF-κB-binding site leads to a tighter binding of NF-κB to TCEd DNA and abolishes its T-cellrestricted activity.…”
Section: Discussionmentioning
confidence: 99%